Rising Waters, Rooted Memories: Cultural Heritage as a resource for climate adaptation in Sinking Cities - Marit Berger, Hilke; Erbach, Teresa; Kuehn, Annika; Possmann, Jan-Philipp; S. Langendijk, Gaby (Journal of Delta Urbanism, 2024)
Communities around the world are facing climate change impacts with coastal communities being particularly vulnerable. While there is a growing awareness of the pivotal role of culture in adaptation, there is a lack of practical approaches for the incorporation of culture in adaptation planning. Skills and knowledge for today´s adaptation challenges can be drawn from cultural heritage since the confrontation with climatic changes and extreme weather events are an elementary feature in human history. We argue that cultural heritage is a rich resource in this context and describe five functionalities of heritage. It can be used to transfer knowledge, to process loss, to strengthen community resilience, to change paradigms in adaptation practice, and to find socially accepted solutions in post-disaster reconstruction. The transdisciplinary research project Sinking Cities: Cultural Heritage as a transformational resource focuses on the potential of cultural institutions and artists in using heritage to support climate adaptation in coastal communities.